The Employment Effect of Innovation: Evidence from Bangladesh and Pakistan (The Pakistan Development Review, 2017)
The analysis of the impact of innovation on employment growth is an important topic for policy-makers. Unemployment is an important social topic, and the effects of innovation on employment are often poorly understood. Despite the significance of this relationship, very few studies on this topic are yet available for developing countries compared with the developed ones. This paper contributes to this scant literature by investigating the employment effects of innovation for two South Asian developing countries: Bangladesh and Pakistan. We further analyse whether this relationship shows country-specific and industry-specific differences. Our analysis shows that both product and process innovation spur employment in this region as a whole, in both low-tech and high-tech industries, even after controlling for a number of firm-specific characteristics. Moreover, although both innovation types also have significant, positive impacts on employment growth of all Bangladeshi and of all Pakistani firms separately, they are important factors for employment growth of only high-tech Bangladeshi firms and of only low-tech Pakistani firms. Contrary to most previous studies, we witness an insignificant effect of growth of labour cost on employment growth, perhaps due to the availability of cheaper labour force compared with the developed countries. We notice that some of the innovation determinants exert different influences across industries and across both countries. The same holds true for the determinants of employment growth. JEL Classification: J23, O31, O33 Keywords: Bangladesh, Employment Growth, Pakistan, Product Innovation, Process Innovation